A critical discourse analysis of Canadian news media coverage of immigration and multiculturalism during the first wave of the 2019 global pandemic (COVID-19) - Arroyo, Angelika (My University, 2024)
This paper aims to examine how Canadian news media framed immigration and multiculturalism during the first wave of the pandemic, between January and July of the year 2020, focusing on determining and identifying patterns in the media coverage of three different major Canadian news outlets (CBC, the National Post, and the Globe and Mail). This study utilized critical discourse analysis (CDA), employing media framing as one of its theoretical frameworks, to deconstruct underlying meanings in the selected articles, conceptualize thematic descriptions, and better understand the representation of ethnic and racial minorities in Canada within the construction of the text.
Presented on April 19, 2024 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: immigration; multiculturalism; critical discourse analysis; COVID-19